Project-Based Construction Education with Simulations in a Gaming Environment - Goedert, James D.; Rokooei, Saeed (International journal of construction education and research, 2016)
Virtual Interactive Construction Education, (VICE)-Bridge, is a project-based pedagogical approach delivered in a simulated environment. The long-term goal of VICE is to develop a series of project-oriented simulations as serious games that deliver construction education in a situated context. VICE improves understanding at a level that parallels real world experiences. The project orientation allows the introduction of subjects for the context in which it is needed. Socio-demographic information is collected and matched to performance measures that include items like number of consultant hits, time to complete exercises, number of attempts, project cost and duration. Twenty-six college level construction students from a methods and equipment course completed the game. Performance was measured with pre- and post-construction content knowledge exercises consistent with the course content, performance measures built into the game, self-assessment surveys, and an exit survey. This project is unique in that it uses simulation in an educational game environment to introduce construction subject matter as needed within a project orientation. The project was shown to be both effective and engaging using evaluation techniques based on best practices for educational gaming research.